Who gets the information? Gender, power and equity considerations in the design of climate services for farmers - Tall, Arame; Kristjanson, Patricia M.; Chaudhury, M.; McKune, Sarah; Zougmoré, Robert B. (2014)
Central to understanding the usefulness of climate and weather forecasts in support of agricultural decision-making is addressing the issue of who receives what information. Many contend that improved climate forecasts since the late 1990s have had limited impact on smallholder farming communities in Africa and across the developing world. However, power and privilege may determine who has access to appropriate climate and advisory services within those communities.